Perbandingan Karakteristik Mutu Biobriket Kulit Durian Dan Jenis Briket Arang Berdasarkan Persentase Volatile Matter - Irhamni Irhamni; Saudah Saudah; Diana Diana; Ernilasari Ernilasari; Mulia Aria Suzanni; Lukmanul Hakim (Fakultas Teknik, 2018)
Bioarang is charcoal (one type of fuel) made from various kinds of biological materials, for example wood, twigs, leaves, grass that can be carbonized. biobriquette is an alternative energy substitute for fuel produced from organic materials or agricultural waste (biomass) that is underutilized, especially durian shell waste. This study aims to look at the comparison of the quality characteristics of the durian shell biobriquette with the type of charcoal based on the percentage of volatile matter. The making of this biobriquette uses 1: 2 pati janeng from the biobriquette weight, the biobriquette particle size is 80 mesh, the cylindrical biobriquette form. The results showed that the biobriquette produced had met the fuel quality standards for households. Level biobriquette of durian shell volatile matter is obtained 6%, and for the type of volatile matter charcoal is 5%. Based on the quality standard for volatile matter is a maximum of 15%. Volatile matter test for biobriquette durian shell obtained can be used as an environmentally friendly fuel.